Demonstration of organic volatile decomposition and bacterial sterilization by miniature dielectric barrier discharges on low-temperature cofired ceramic electrodes - Kim, Duk-jae; Shim, Yeun-keun; Park, Jeongwon; Kim, Hyung-jun; Han, Jeon-geon (IOP PUBLISHING LTD, 2016)
Nonthermal atmospheric-pressure plasma discharge is designed with low-temperature cofired ceramic (LTCC) electrodes to achieve dielectric barrier surface discharge (DBSD). The environmental requirement (below 0.05 ppm) of the amount of byproducts (ozone and NOx) produced during the process was met by optimizing the electrode design to produce a high dielectric barrier discharge for low-voltage (similar to 700 V) operation and minimizing the distance between electrodes to improve the plasma discharging efficiency. The concentrations of volatile organic compounds (VOCs) within interior cabins of commercial vehicles were significantly reduced after 1-h treatment to improve air quality cost-effectively. This atmospheric-pressure plasma process was demonstrated for the sterilization of Escherichia coli to prevent food poisoning during the preservation of food in refrigerators. (C) 2016 The Japan Society of Applied Physics
Keywords: ATMOSPHERIC-PRESSURE PLASMA; SURFACE MODIFICATION; COLD-PLASMA; JET; MECHANISM; COATINGS; ARGON